“Buen Trato” program to improve socio-affective relationships through digital communication in adolescents - Nieto-Ariza, Mary Carmen; López-Pastor, Ana Teresa; Jiménez-Sánchez, Álvaro (Revista Española de Comunicación en Salud, 2024)
Introduction: In recent years, the use of digital social networks has increased among adolescents. This has led to a change in the way they relate interpersonally and socioaffectively, with great benefits, but also with relevant detriments. Objectives: This study aims to analyze and evaluate the effectiveness of the “Buen Trato” program carried out in an educational institution with adolescents, which consists of learning to use digital communication to improve these relationships. Methodology: 15 students of second year of Secundary Education participated during six months in different workshops and activities. A pretest and a posttest were carried out, as well as a series of semi-estructured interviews with different authorities of the educational center, the Youth Council of the city of Segovia (Spain) and the ANAR Foundation. Results: The statistically significant differences point to an awareness of the use of these computer applications when it comes to using them for their socio-affective relationships. The responses to the interviews show that the Buen Trato program has been of great help to students, family members and teachers. Conclusion: It is determined that the dynamics used can serve as a great reference for other centers, as long as they are necessarily adapted to the different socio-cultural contexts and technological advances.
Keywords: media literacy; health communication; “Buen trato” program; socio-affective relationships; digital social networks